2019
DOI: 10.18203/2349-2902.isj20191894
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of MRI fistulogram and X-ray fistulography with operative findings: in fistula in ano

Abstract: Background: The current study has attempted to evaluate the effectiveness and diagnostic accuracy of MRI fistulogram over X-ray fistulography by comparing their findings with intraoperative findings.Methods: A hospital based prospective study was conducted at Dr. D.Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune with 60 patients to compare the findings of MRI fistulogram and X-ray fistulography with operative finding in fistula in ano. The study was carried out with following two groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Further, it may create a wrong impression of the presence of an extrasphincteric track. The fourth important drawback is that fistulography is an invasive technique and may result in dissemination of sepsis [3,10].…”
Section: X-ray Fistulographymentioning
confidence: 99%
“…Further, it may create a wrong impression of the presence of an extrasphincteric track. The fourth important drawback is that fistulography is an invasive technique and may result in dissemination of sepsis [3,10].…”
Section: X-ray Fistulographymentioning
confidence: 99%
“…In another study, both MRI and X-ray fistulography findings done in two separate groups of patients were compared with the surgical findings and found near 100% sensitivity of MRI, while that of X-ray fistulography was very low. 15 Sofic et al compared the findings of X-Ray, computed tomography (CT), and MRI fistulography in 24 cases and found transphincteric fistulae to be the most common (29.16%); intersphincteric (25%), recto-vaginal (25%), extrasphincteric (12.5%), suprasphincteric (8.33%), and abscess collections were seen in (16.6%) patients. The authors found the accuracy of the classification of fistulas on X-ray fistulography to be 37.5%, CT fistulography 50%, and MRI 83.3%.…”
Section: Discussionmentioning
confidence: 99%